Looney Tunes All Stars v.1 - Dante, Joe.; Goldberg, Bill, 1966-; Heather Locklear; Jenna Elfman; Joan Cusack; Steve Martin; Timothy Dalton; Brendan Fraser (USA Warner Bros. Pictures, 2003)
Fed up with all the attention going to Bugs Bunny, Daffy Duck quits Hollywood, teams up with recently-fired stuntman Damien Drake Jr.(Fraser) and embarks on a round-the-world adventure, along with Bugs and The VP of Warner Bros (Elfman). Their mission? Find Damien's father, and the missing blue diamond... and stay one step ahead of The Acme Corp., who wants the diamond for thier own purposes.
The Looney Tunes search for a mans missing father and the mythical Blue Diamond.
Larry Doyle
Language(s): English, Polish, Czech, Turkish
Subtitle(s): English, Turkish
Keywords: Adventure; Animation; Comedy; Fantasy; Action